TINJAUAN YURIDIS PERJANJIAN BISNIS WARALABA (FRANCHISE) ANTARA FRANCHISOR DAN FRANCHISEE DALAM DINAMIKA PEREKONOMIAN DI INDONESIA - Rustinah Hariyani (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractMany franchise businesses inIndonesia. This business is a business that is very easy to make a profit. To start this business, both prospective franchisees and franchisors must enter a written franchise agreement. This franchise business is also closely related to trademarks and trade secrets, so that in this business it is closely related to the legal aspects of agreements and intellectual property law. Legal aspects in the franchise business agreement (franchise) between the franchisor and the franchisee as a form of economic dynamics in Indonesia, including : (1) relating to the law of the agreement (Civil Code), in which the franchise business cooperation requires an agreement written and agreement terms as regulated in the Civil Code, and (2) relating to intellectual property rights, which are franchise criteria in which intellectual property rights have been registered in accordance with Article 3 of Government Regulation Number 42 Year 2007, especially trademarks and trade secrets. Legal protection for the franchisor and franchisee in the franchise agreement as stipulated in Government Regulation No. 42/2007 concerning Franchising, carried out through franchising registration and recording a franchise agreement. Keywords : Agreement, Business, Franchise